2021
DOI: 10.3390/rs13071355
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Cotton Mapping Using Time Series of Sentinel-2 Images

Abstract: Large-scale crop mapping is essential for agricultural management. Phenological variation often exists in the same crop due to different climatic regions or practice management, resulting in current classification models requiring sufficient training samples from different regions. However, the cost of sample collection is more time-consuming, costly, and labor-intensive, so it is necessary to develop automatic crop mapping models that require only a few samples and can be extended to a large area. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These features are indicative of boll opening and senescence signals, suggesting that the boll opening stage is the most critical phenological stage for cotton identification. This finding is consistent with previous studies and is in line with cotton's actual physical and biochemical characteristics [25,27]. In time-series dynamic features, the harmonic coefficients of cos (3πt), sin (3πt) and constant terms were found to be relatively more important, as demonstrated in Figure 6.…”
Section: Performance Of Feature Optimization Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…These features are indicative of boll opening and senescence signals, suggesting that the boll opening stage is the most critical phenological stage for cotton identification. This finding is consistent with previous studies and is in line with cotton's actual physical and biochemical characteristics [25,27]. In time-series dynamic features, the harmonic coefficients of cos (3πt), sin (3πt) and constant terms were found to be relatively more important, as demonstrated in Figure 6.…”
Section: Performance Of Feature Optimization Methodssupporting
confidence: 92%
“…Our results have demonstrated that incorporating multiple spectral features at different phenological stages can significantly enhance the classification accuracy compared to relying solely on NDVI and EVI throughout the entire phenological period. Further, some studies have solely employed individual phenological stages for cotton extraction [27,61], which could heighten the probability of confusion between cotton and other crops with similar spectral characteristics (e.g., maize and cotton) [1].…”
Section: Reasonability Of Tmpfmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cotton has white fibre, and a small amount of cotton has colored fibre in Xinjiang 83 , 84 . A few recent studies have reported that the phenological feature in the boll-opening stage could be used for cotton mapping 11 and cotton yield estimation 85 – 88 . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenge to produce a fine cultivation map of cotton throughout Xinjiang 7 , probably because such a task needs a powerful platform with high storage and computing capabilities 8 ; it needs enough high-quality and evenly distributed samples due to the high spatial heterogeneity 9 ; and it needs models with high universality, accuracy, and transferability to address issues like bad weather 10 . To date, numerous studies have mainly focused on Xinjiang cotton mapping at county 1,11,12 , prefecture 13 , region 7,14 , and province scales 15,16 . Although we recently have produced the 500 m nationwide cotton maps in 2016 and 2018 that were included in the reports on remote sensing monitoring of China Sustainable Development 15,16 , both of them demonstrated limitations and disadvantages in practical precision management and decision making due to the very low spatial resolutions.…”
Section: Background and Summarymentioning
confidence: 99%